Modern problems of the physics of liquid systems : selected reviews from the 8th International Conference "Physics of Liquid Matter: Modern Problems", Kyiv, Ukraine, May 18-22, 2018 /: selected reviews from the 8th International Conference "Physics of Liquid Matter: Modern Problems", Kyiv, Ukraine, May 18-22, 2018. (2019) - Unknown
No abstract available